Landscape of protein-protein interactions in Drosophila immune deficiency signaling during bacterial challenge - Fukuyama, Hidehiro; Verdier, Yann; Guan, Yongsheng; Makino-Okamura, Chieko; Shilova, Victoria; Liu, Xi; Maksoud, Elie; Matsubayashi, Jun; Haddad, Iman; Spirohn, Kerstin; Ono, Kenichiro; Hetru, Charles; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
The Drosophila defense against pathogens largely relies on the activation of two signaling pathways: immune deficiency (IMD) and Toll. The IMD pathway is triggered mainly by Gram-negative bacteria, whereas the Toll pathway responds predominantly to Gram-positive bacteria and fungi. The activation of these pathways leads to the rapid induction of numerous NF-κB-induced immune response genes, including antimicrobial peptide genes. The IMD pathway shows significant similarities with the TNF receptor pathway. Recent evidence indicates that the IMD pathway is also activated in response to various noninfectious stimuli (i.e., inflammatory-like reactions). To gain a better understanding of the molecular machinery underlying the pleiotropic functions of this pathway, we first performed a comprehensive proteomics analysis to identify the proteins interacting with the 11 canonical members of the pathway initially identified by genetic studies. We identified 369 interacting proteins (corresponding to 291 genes) in heat-killed Escherichia coli-stimulated Drosophila S2 cells, 92% of which have human orthologs. A comparative analysis of gene ontology from fly or human gene annotation databases points to four significant common categories: (i) the NuA4, nucleosome acetyltransferase of H4, histone acetyltransferase complex, (ii) the switching defective/sucrose nonfermenting-type chromatin remodeling complex, (iii) transcription coactivator activity, and (iv) translation factor activity. Here we demonstrate that sumoylation of the IκB kinase homolog immune response-deficient 5 plays an important role in the induction of antimicrobial peptide genes through a highly conserved sumoylation consensus site during bacterial challenge. Taken together, the proteomics data presented here provide a unique avenue for a comparative functional analysis of proteins involved in innate immune reactions in flies and mammals.
Gesehen am 06.12.2021